2006 IEEE Nuclear Science Symposium Conference Record 2006
DOI: 10.1109/nssmic.2006.353845
|View full text |Cite
|
Sign up to set email alerts
|

Monte Carlo Simulation Study of Several Camera Designs for the PET Component of a Dedicated Breast PET/CT Scanner

Abstract: In this study we used Monte Carlo simulations to analyze the patient imaging performance of a range of camera geometries for the PET portion of a dedicated pendant breast PET/CT system. Performance was assessed by comparing NEC, rates, and scatter fractions for a range of injected FDG activities. The same LSO block detector (9x9 arrays of 3 mm x 3 mm x 20 mm crystals and 3.3 mm pitch) was used to compose a cylindrical, split-ring, five-sided box, and a planar dual-headed system. To simulate the patient an anth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Greater gains would be possible if the detectors were operated with a lesser separation distance, but this is not likely to be practical for tomographic imaging of typical breast sizes. The system sensitivity may be improved in a future system by utilizing more detector material and/or a different geometry (Bowen et al , 2006). …”
Section: Discussionmentioning
confidence: 99%
“…Greater gains would be possible if the detectors were operated with a lesser separation distance, but this is not likely to be practical for tomographic imaging of typical breast sizes. The system sensitivity may be improved in a future system by utilizing more detector material and/or a different geometry (Bowen et al , 2006). …”
Section: Discussionmentioning
confidence: 99%
“…23) [85]. Positron emission mammography (PEM) systems consist of two parallel detectors that do not rotate, and these provide slice data parallel to detectors using focal plane tomographic techniques (or limited-angle tomography) (Fig.…”
Section: Breast-dedicated Positron Imaging Systemsmentioning
confidence: 99%
“…Widening the angular coverage by rotating the planar detectors or utilizing a full ring or rectangular camera geometry provide the most direct ways of coping with the limitations of limited-angle tomography and of providing isotropic resolution in all three dimensions. High geometrical detection efficiency can be achieved using the full ring and the rectangular designs, and simulation studies have shown that the count rate performances of these cameras are better than those of cameras with two parallel detectors [85,90]. On the other hand, rotating planar detectors allow easier access to the breast for biopsy, although some photons loss occurs at gaps between the detectors [89].…”
Section: Breast-dedicated Positron Imaging Systemsmentioning
confidence: 99%